Are transparent double-skin facades effective for energy retrofit? Answers for an office building - with and without photovoltaic integration. Issue 1 (31st March 2022) - Ascione, Fabrizio; Bianco, Nicola; de Rossi, Filippo; Iovane, Teresa; Mauro, Gerardo Maria
ABSTRACT: Buildings account for an important share of global energy consumption and CO2 emissions, so increasing energy efficiency in buildings is essential to ensure an energy transition and sustainable development. In this study, we evaluate the energy benefits obtained through the application of a double-skin façade (passive façade). Subsequently, this is combined first with an airflow network and a control logic for opening windows (active façade) and secondly with transparent photovoltaic modules. The proposed measures are applied to an office building at the University of Naples Federico II. Building's thermal and energy performance are evaluated using EnergyPlus software, starting from validated energy demands of the base buildings. Both passive and active façade provided a reduction in primary energy consumption for space conditioning, of about 17% and 28%, respectively, and in the total primary energy consumption, of about 4% and 9%, respectively. The best solution, with the maximum energy saving in total primary energy consumption, approximately 20%, is achieved with the active façade and with 80% of the outer layer of the double-skin façade covered by PV modules. The results show that transparent double-skin facades are promising and effective for energy retrofit. Graphical abstract: uf0001